Characterisation, Chain Conformation and Antifatigue Effect of Steamed Ginseng Polysaccharides With Different Molecular Weight - Jiao, Lili; Li, Junming; Liu, Furao; Wang, Jing; Jiang, Peng; Li, Bo; Li, Hui; Chen, Changbao; Wu, Wei (Frontiers in Pharmacology, 2021)
Two polysaccharides were obtained from steamed ginseng via ultrafiltration, and their physical–chemical properties, solution properties and antifatigue activities were studied. WSGP-S3 and WSGP-G3 were acid heteropolysaccharides with the molecular weights of 2.03 × 104 and 4.86 × 104, respectively. They were composed of different molar ratios of the monosaccharides Rha, GlcA, GalA, Glc, Gal and Ara. The results of size-exclusion chromatography–multiangle laser light scattering analysis, Conge red staining and Circular dichroism spectroscopy revealed that WSGP-S3 exhibited a random conformation of branched clusters in solution. By contrast, WSGP-G3 exhibited an ordered conformation, including helix-like conformations in aqueous solution. Antifatigue activity tests proved that WSGP-S3 markedly prolonged the exhaustive swimming time of fatigued mice; increased liver and muscle glycogen levels and superoxide dismutase, catalase, glutathione peroxidase activities and decreased blood lactic acid, nitrogen and malondialdehyde levels compared with the control treatment. Moreover, it enhanced spleen cell proliferation in fatigued mice. By contrast, WSGP-G3 had no significant effect on fatigued mice. The results showed that WSGP-S3 might have a major contribution to the antifatigue effects of steamed ginseng polysaccharides and could be a potential anti-fatigue polysaccharide.